Design and fabrication of a foldable 3D silicon based package for solid state lighting applications. (17th April 2015) - Sokolovskij, R; Liu, P; van Zeijl, H W; Mimoun, B; Zhang, G Q
Abstract: Miniaturization of solid state lighting (SSL) luminaires as well as reduction of packaging and assembly costs are of prime interest for the SSL lighting industry. A novel silicon based LED package for lighting applications is presented in this paper. The proposed design consists of 5 rigid Si tiles connected by flexible polyimide hinges with embedded interconnects (ICs). Electrical, optical and thermal characteristics were taken into consideration during design. The fabrication process involved polyimide (PI) application and patterning, aluminium interconnect integration in the flexible hinge, LED reflector cavity formation and metalization followed by through wafer DRIE etching for chip formation and release. A method to connect chip front to backside without TSVs was also integrated into the process. Post-fabrication wafer level assembly included LED mounting and wirebond, phosphor-based colour conversion and silicone encapsulation. The package formation was finalized by vacuum assisted wrapping around an assembly structure to form a 3D geometry, which is beneficial for omnidirectional lighting. Bending tests were performed on the flexible ICs and optical performance at different temperatures was evaluated. It is suggested that 3D packages can be expanded to platforms for miniaturized luminaire applications by combining monolithic silicon integration and system-in-package (SiP) technologies.